Old Delivery and Modern Demagogy: How Ancient Oratorical Style and Delivery can Help us to Understand Modern Populist Speakers - Balbo, Andrea (Informal Logic, 2019)
My paper aims to find potential elements of comparison between ancient oratoria popularis and modern populist oratory. I will consider case studies drawn from Gracchan speech style and from the oratory of Donald Trump.